(3QSGdI aj GdOhQ hGdJSdSds - (3eMeO SYjO Hf Ydj Hf YHO GdbGOQ Hf eMjj GdOjf GdMSfj GdLRGFQj , (B1390 (3gčs ((3GdeDdas)
(3ChdgG (B:s
(3HYO GdHSedI ; hGdJUdjI hGdMeOdI hHYO aEfc GdJeSJ efj CjVG Cf fHjf dc hLg GSJMGdI GdOhQ hGdJSdSd aGYde hdOj GhdG Cf gPg GdCLQGe GdeMShSI eecfI dJQcHgG ef GdLhGgQ GdeaQOI hbO JbQQ Cf cd eQcH eecf dGMJjGLg Edi LRFgs
(3BNQgG (B:s
(3hef RYe GfLUGQ LgGJ GdHGQj JYGdi ajeG YdefGg adG jNai JMceg EP dG jdRe ef YOe Ydi EKHGJ GdTQY Gh fgjg aj faS GdCeQ hdG GKHGJg hGdJMce Jcda GdMce HdG Odjd hHGddg GdJhajbs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds